Dinamika vegetativnych funkcij pri adaptacii k fiziceskim nagruzkam - Artemenkov, A. A. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The purpose of the research was the studying of the dynamics of vegetative functions and the coupling of cardiorespiratory parameters at adaptation to physical loadings.